Pengaruh Kualitas Pelayanan Dan Fasilitas Terhadap Kepuasan Mahasiswa Kuliah Di Kampus Bisnis Umar Usman - Asep Hendriana; Iwan Pratama (JAS-PT (Jurnal Analisis Sistem Pendidikan Tinggi Indonesia), 2022)
This study aims to find out how much influence price, and promotion on the decision of students to choose to study at Kampus Bisnis Umar Usman, this research method is a quantitative research method, the population in this study is Umar Usman Business campus students in 2021/2022, The sample used in this study is 48 students with an accidental sampling approach (accidental sampling). The results of the preliminary analysis carried out show that the indicators used are valid for measuring existing variables. The results of the next analysis found that of the three variables used in this study, from the results of testing the hypothesis between Prices (X1) affecting the decision (Y) of students to restore college. The results obtained were 8.5% followed by the promotion variable with a regression coefficient of 15.6%, concluding, that price and promotion had a positive and significant effect on the decision of students to choose to study at the Umar Usman Business campus was 16.8% Keywords: Promotion, price, decision to choose